THE PECULIARITIES OF FOREIGN LANGUAGE TRAINING OF TECHNICAL UNIVERSITY STUDENTS IN CONDITIONS OF COMPETENCE APPROACH - Angelina Olegovna Bagateeva; Yuliya Viktorovna Ryseva; Aida Alegovna Vasilyeva; Rimma Salavatovna Garaeva (Sovremennye Issledovaniâ Socialʹnyh Problem, 2018)
The article deals with the concepts of “communicative competence” and “foreign language communicative competence”. The research is based on such methods as observation, analysis, and modeling method. The article presents the author’s interpretation of the concept of foreign language communicative competence of students from the position of competence and system approaches. The authors give the component composition of foreign language communicative competence from the point of view of various researchers, define its structural elements. On the basis of the analysis, the model of modular technology of foreign language training of technical university students is constructed, the characteristic of its structural components is given, and also the results of its implementation in the process of foreign language training technical university students are described. The use of modular technology in foreign language training of technical university students allows to obtain a high level of foreign language communicative competence. The model of modular technology of foreign language training of technical university students is developed. The results of the study can be applied to the foreign language training of students not only technical universities, but others as well.